Muhammad Cheng Ho Pasuruan Da’wah Management Picture In Conserving The Mosque: Muhammad Cheng Ho Pasuruan Da’wah Management Picture In Conserving The Mosque - Halimatus, Nur; Astutik, Sri (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2023)
The Muhammad Cheng Ho Mosque is one of the mosques that has a unique architectural form with Chinese characteristics, this mosque is often also called a tourist mosque because many visitors come with offers of strategic places, and there is also a souvenir center and the Cuggrang museum next to it  , but it is a challenge for takmir and administrators in managin g the mosque to remain attractive to local residents with residents who can be said to be not so close.  So the first question to be answered in this study is "How is the portrait of the management of the da'wah used at the Muhammad Cheng Ho mosque to continue to preserve the mosque?  This study uses a descriptive qualitative method, with a research design of data collection, analyzing and then describing.  With the following research results, there is an application of sharia strategic management that is enforced in organizing the takmir of this mosque, first;  tasks that are initiated based on monotheism, Second;  the profit is balanced between the world - ukhrawi.  Third;  fourth mardatillah motivation;  ubudiyah's belief in carrying out the fifth responsibility;  ihsaniyah awareness.  By procuring activities, starting from weekly, such as women's taklim assemblies, monthly activities, in the form of sholawat assemblies, qiyamullail prayers in congregation, as well as annual activities, PBHI celebrations for example.  As well as the preparation of free guidance for converts.  As well as financial management apart from special charity boxes to utilization of facilities.